Organisasi dan Desain Pengembangan Kurikulum PAI - Ghamal Sholeh Hutomo; Tasman Hamami (At-Tafkir, 2020)
Islamic education curriculum is not separated from its relation to the basicand objectives of Islamic education. Some parts of the curriculum materials can bedeveloped by the demands of the times and the human environment but considered thetimes and the human environment, but considered that the curriculum of Islamiceducation should be substantive in the purpose of Islamic education. The curriculumorganization is considered to be able to achieve that goal. Acting as a determinant ofhow a defection will take place, of course, this curriculum organization is one of the important factors. Curriculum design is a framework in drafting curriculum organization and is a preparation of one component of the curriculum that is the content of curriculum material. This research uses library research by analyzing the data, documents related to the discussion is systematically analyzed. The purpose of this research is to know the form of the Islamic Education curriculum organization, the design principles of the Islamic Education curriculum, and the Islamic Education curriculum design.